Psychological and sociocultural adaptations of International Students in Malaysian Public Universities. - Abd Razak, Nordin (Universiti Sains Malaysia, 2017)
This study developed and empirically tested a conceptual model capturing the factors impacting students' cross-cultural adaptation and the outcomes resulting from such adaption. Data were obtained from a sample of international postgraduate students from six Malaysian public universities using a structured questionnaire. Structural equation modelling using SmartPLS was utilised to analyse the data.